STANDARDIZATION OF “FLUCAM” OINTMENT - Alimkulova Komila Zokirovna; Pulatova Dildora Kahramonovna; Ikramova Mashkura Shukhratovna; Urmanova Flyura Faridovna; Todjiyev Jamoliddin Nasiriddinovich (Research Focus International Scientific Journal, 2025)
In recent years, the interest of specialists in the problem of immunocorrective therapy has increased significantly, primarily due to the significant increase in immunodeficiency conditions and the understanding that the development of most pathological processes is caused by a disruption in the functions of the immune system. Immunotropic drugs of plant origin have a gentle effect on the body, restore immunity, mobilize the reserve defense mechanism, and increase the effectiveness of therapy due to the content of various biologically active substances. The inclusion of plant immunomodulators that affect both humoral and cellular immune responses, as well as factors of non-specific resistance of the body, in the treatment of various immunodeficiency conditions makes it possible to increase the effectiveness of the therapy. Taking into account the above circumstances, the authors obtained a dry extract from a multi-component plant composition, which served as the basis for creating an ointment with immunomodulatory action “Flucam”. The latter, being practically non-toxic and having no side effects on the body, exhibits a pronounced immunomodulatory effect, surpassing in its activity known foreign analogues. In order to promote the said ointment in medical practice, studies have been conducted on its standardization. The characteristics of authenticity and quality indicators of the ointment have been determined, and methodological techniques for the qualitative and quantitative determination of the main active substances - glycyrrhizic acid and tannins - have been developed. At the same time, an important place is given to the so-called "end-to-end standardization", which is based on the assessment of the quality of the original plant composition, dry extract and the ointment obtained from it by the content of the same biologically active compounds. This, to a certain extent, allows for a sufficient guarantee of the quality and constant composition of the finished product.